Synergizing Human Resource Management and Information Technology to Enhance School Management Performance in the Digital Era - Tri Ananda Setiyani; Nur Adzkia Kamilah; Siti Raisyah; Ahmad Suriansyah; Aslamiah Aslamiah (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: This study aims to provide an in-depth analysis of the synergy between human resource (HR) management and the use of information technology (IT) in improving school management performance in the digital era. Digital transformation in education requires schools not only to provide adequate technological infrastructure but also to ensure the readiness and competence of their human resources in operating, managing, and optimizing technology-based systems. This research employs a descriptive qualitative approach, using in-depth interviews with principals, teachers, and administrative staff as key informants. The collected data were analyzed through thematic analysis to identify patterns of collaboration, implementation challenges, and strategic efforts to strengthen the integration of HR and IT within school governance. The results reveal that the integration of IT into school management significantly enhances administrative efficiency, accelerates academic services, improves data accuracy, and increases communication transparency among schools, students, and parents. Digital competence, leadership capacity, and a collaborative work culture emerge as essential factors influencing the successful implementation of digital initiatives. However, several obstacles remain, including limited technological infrastructure, varying levels of technological proficiency among staff, and the lack of continuous professional development programs. This study concludes that strengthening digital competencies, fostering visionary leadership, and developing more comprehensive information systems are crucial strategies for creating modern, adaptive, and sustainable school management practices. Effective synergy between HR and IT not only improves the quality of educational services but also enhances the school’s competitiveness in navigating rapid technological advancements. Keywords: Human Resource Management; Information Technology; School Management; Digital Transformation; Performance Improvement